(untitled) (Journal of Brahmanbaria Medical College, 2026)
Background: Dyslipidemia, characterized by abnormal lipid profiles, is a significant Cardiovascular Risk Factor (CVRF) in the general population and its presence in children and adolescents with Type 1 Diabetes Mellitus (T1DM) is a major concern. The clinical profile of diabetes in children and adolescents under eighteen years of age often includes various complications and associated conditions, demanding comprehensive management. In regions like Bangladesh, T1DM presents unique challenges in terms of incidence and care. Multiple studies have highlighted a considerable prevalence of dyslipidemia in this young T1DM population, with rates varying across different geographical and ethnic cohorts. The primary abnormalities observed typically involve elevated levels of Total Cholesterol (TC) Triglycerides (TG) and Low-Density Lipoprotein Cholesterol (LDL-C), coupled with reduced high-density lipoprotein cholesterol (HDL-C). A strong and consistent association has been established between poor long-term glycemic control, particularly indicated by High Glycosylated Hemoglobin (HbA1c) levels and adverse lipid profiles. Diabetes duration is also often implicated, with longer duration correlating with worse dyslipidemia, thereby accelerating the progression of subclinical atherosclerosis detected early in T1DM youth. Other factors such as body habitus, which can be assessed via anthropometric measurements, and certain dietary intakes may also influence lipid status. The significance of these lipid abnormalities lies in their role in the development of premature atherogenesis and subsequent cardiovascular events. Consequently, there is an established need for rigorous screening, as recommended by major professional bodies and the implementation of therapeutic strategies. Recent findings, including randomized controlled trials, suggest that nonpharmacological interventions like regular exercise can potentially improve cardiovascular risk factors in these adolescents. Methodology: This current study is a systematic review to the published articles and research studies carried out via PubMed and Google scholar. Strategy for article search was by using appropriate key words and title. Conclusion: This systematic review synthesizes the current literature to emphasize the burden of dyslipidemia, its key determinants (Poor glycemic control, diabetes duration etc.) and the imperative for early risk mitigation in pediatric and adolescent T1DM. The overall implication is the need for rigorous screening and therapeutic strategies to prevent premature cardiovascular events. JBRMC, Volume 08 Issue 01 January 2026 ; 41-46